Multiple Challenges and Opportunities for Biogas Dissemination in Indonesia - Ibnu Budiman; Raushanfikr Muthahhari; Ceylan Kaynak; Fabian Reichwein; Wandi Zhang (Indonesian Journal of Energy, 2018)
More than the half of Indonesian households primarily rely upon firewood for cooking. To overcomecthis problem, multiple initiatives established the decentralized biogas programs. This paper aims to analyze the environmental problem of firewood cooking and to find out various challenges and opportunities for biogas dissemination in rural areas in Indonesia. The method used in this paper is literature review with frameworks of DPSIR and stakeholder matrix. The result found that the firewood cooking is adversely impacting local wooded ecosystems, deforestation rate and negative effect on human respiratory health. The biogas programme is still not able to replace the firewood use. The research found that it is caused by two major challenges. The first one is the issue with the project's approach in which biogas programmes are still dominated by the government grants. This situation leads to community dependency on the grant, lack of investment and low demand and market in this sector. The second challenge is the technology part where many biogas digesters were not operated due to the low quality of installation, and lack of knowledge and skill of the biogas user about the maintenance and installation of the digester. This study suggests that there is the opportunity to improve the approach of governmental biogas programme. It has to involve more roles from non-state actors. In the user side, the farmers as majority user also should be trained properly how to maintain the biogas installations. As the solution, instead of the full grant, the programme can reduce the percentage of subsidy and turn the cost to provide more digesters and training. Key stakeholders need to have cooperation to increase the quality and quantity of the biogas dissemination.